INTEGRATING ARTIFICIAL INTELLIGENCE INTO ENGLISH LANGUAGE TEACHING: A METHODOLOGICAL APPROACH TO DEVELOPING STUDENTS’ WRITING AND SPEAKING COMPETENCIES - Jabborberganova Hurriyat., (TADQIQOTLAR, 2026)
Abstract: This work presents a comprehensive methodological approach to the integration of artificial intelligence (AI) into English language teaching (ELT), with a focus  on  enhancing  students’  writing  and  speaking  competencies.  The  discussion unpacks the evolving role of AI-driven tools, their pedagogical implications, benefits, challenges,  and  critical  considerations  for  sustainable  implementation  in  various educational contexts. Special attention is paid to the effectiveness of AI in personalized instruction,  feedback  mechanisms,  collaborative  and  communicative  competence development, and student motivation. The work draws on recent academic research, practical case studies, and theoretical frameworks to propose a holistic, ethical, and inclusive  strategy  for  integrating  AI  into  ELT.  The  conclusion  highlights  future prospects  and  challenges,  and  the  reference  section  offers  recent  studies  to  guide further exploration.